Providing Coordinated, Immediate, Trauma-Focused, and Interdisciplinary Responses to Children Exposed to Severe Intimate Partner Violence: Assessing Feasibility of a Collaborative Model - Stylianou, Amanda M. (Journal of interpersonal violence, 2021)
Despite the known consequences associated with children’s exposure to intimate partner violence (IPV), numerous children exposed to IPV never access victim services and/or mental health treatment. Informed by the Child Development-Community Policing Program (CD-CP), the Child Trauma Response Team (CTRT) is designed to provide a coordinated, immediate, trauma-informed, and interdisciplinary response to children, adolescents, and their impacted family members who are exposed to severe IPV. The aim of this study was to explore the feasibility of the CTRT from the perspective of the key stakeholders and to identify what facilitated and/or hindered the collaborative model. Interviews were conducted with all 12 CTRT stakeholders of whom three worked for law enforcement, four worked for the district attorney’s office, four worked for the nonprofit victim service organization, and one worked for the city office funding the pilot. Results indicated that the CTRT program evolved through a cyclical process including (a) implementing and enhancing program services, (b) defining and nurturing partner relationships, and (c) shifting practices among partnering agencies. The results provide concrete tools and practices that were successful in the CTRT pilot implementation. Despite the potential barriers to successful multidisciplinary collaborations, it is critical that we invest in developing and implementing collaborative intervention models in the IPV field. The CTRT model is an innovative model that conducts multidisciplinary coordinated outreach to families experiencing severe IPV to enhance family engagement in services and, when appropriate, in the criminal justice process.